Pengembangan e-LKPD Materi Kimia Hijau Berbasis PjBL Terintegrasi Chemo-Entrepreneurship Berorientasi Kreativitas Peserta Didik pada Fase E SMA: Penelitian - Grace Landong Olyvia Panjaitan; Epinur; Harizon (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research was motivated by limited interactive, contextual teaching materials supporting green chemistry learning. It aimed to develop PjBL-based green chemistry e-LKPD integrating Chemo-Entrepreneurship and oriented toward student creativity. The e-LKPD was developed using the Lee & Owens model, limited to the development stage. Data were collected through interviews, student needs questionnaires, expert validation sheets, and student response questionnaires, analyzed qualitatively and quantitatively. Results showed the e-LKPD was highly feasible, with a material expert validation score of 90.6%, media expert validation of 92.8%, and teacher assessment of 86.2%. Product trials in one-on-one tests showed 81.6% correct answers in the very good category, while small group trials obtained 89.4% positive responses, also in the very good category. Therefore, the developed e-LKPD is concluded to be highly feasible for use as teaching material in green chemistry learning.